Analisis Minat Anak Usia 10-12 Tahun Terhadap Permainan Tradisional di Desa Honggosoco - Nurul Hidayah; Siti Masfuah; Su'ad Su'ad (STKIP Andi Matappa Pangkep, 2021)
Background of this research is that children rarely play traditional games and children more often play modern games, one of which is playing gadgets. This research is a descriptive qualitative research. The research location is in Desa Honggosoco RT 03 RW 01, while the reseach subjects are 5 children aged 10-12 years and 5 parents. This study aims to analyze the interest of children aged 10-12 years in traditional gemes in Desa Honggosoco, and analyze factors influencing the interest of children aged 10-12 years toward traditional games in Desa Honggosoco. Data collection techniques used are interviews, observation, documentation, and recording. The results showed that some of the children had interest criteria that were less interested in traditional games, but there were still children who had interested criteria and were very interested. Factors that affect the interest of children who have the criteria of less interest are lack of attention, lack of curiosity, family, and the environment. Factors that affect the interests of those who have interest criteria are good concentration of attention and family, while for children who have high interest criteria, children are very interested, namely good concentration of attention, needs, family, and environment.